Avenida Josefa Taveira: estudo do uso e ocupação do solo na perspectiva comercial. - Santos, Kaio César Pereira de Medeiros. (2013)
This paper addresses the use and occupation of land on Avenue Josefa Taveira, in business perspective, through a cutout in the path is the roundabout Banking / Mangabeira until the signal from Public Market neighborhood in evidence. The method used was descriptive and reflective approach to the process of transformation that capitalism promotes the area in question, in this case, the formation of intra urban and especially the changes implemented by capital. Currently, Mangabeira is inserted as a sub-center of the city of João Pessoa Avenue and Josefa Taveira exerts greater centrality in this space because it has a variety of shops and services offered to the population, more affordable to the public, making people moving less and less to the center of João Pessoa. For this work we used location maps of the study areas, trying to João Pessoa succinctly broader neighborhood Mangabeira and with greater emphasis on Avenue Josefa Taveira. In addition to maps, we used several scientific works such as monographs, dissertations, but also, using data available in organs like the IBGE (Brazilian Institute of Geography and Statistics), Department of Planning, Urban Development and Environment João Pessoa (SEPLAN) and images, in order to analyze the changes in urban space Mangabeira and acquire information pertinent to the research. In this context, it is expected that the work will contribute to the expansion of the study of the socio spatial Avenue.